(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2021)
The present work gives a conception for the evaluation of the infrastructure associated to nature attractions in function of the local development that had not been formulated before and fill the existing shortage from theoretical-mythological point of view, which is conceived with a local vision, validating the process in the municipality of Guisa, province of Granma. The foundations for this conception are set from the redefinition of the “touristic resource” taking into account the international and national experience. From the determination of local touristic potential, a procedure for the evaluation of the infrastructure and the Popular Power and Administration organs that will contribute to the local decision making process related to the nature tourism development.